Association between atherogenic index of plasma and post-stroke depression: a cross-sectional study - Demin Kong; Wei Zou (European Journal of Psychotraumatology)
Background: Few studies have established a link between the atherogenic index of plasma (AIP) and post-stroke depression (PSD). This study aims to further investigate the potential relationship between the AIP and PSD, and to provide references for the prevention and prognosis management of patients with PSD.Methods: A cross-sectional study was conducted using data from participants in the National Health and Nutrition Examination Survey from 2005 to 2018. Inclusion criteria required complete data on the AIP, stroke history, and depression status. Weighted logistic regression models and restricted cubic splines (RCS) were employed to examine the association between the AIP and PSD. By subgroup and interaction analyses, the stability associated with AIP and PSD was assessed between different subgroups.Results: Among the 32,364 participants ultimately enrolled in the study, 482 were diagnosed with PSD. In the weighted multivariate logistic regression adjustment model 3, AIP, as a continuous variable, was positively associated with the risk of PSD [odds ratio (OR) = 1.85, 95% confidence interval (CI): 1.18, 2.91; P = 0.007]. After the quartile classification of AIP, the adjusted model 3 showed that the risk of PSD in group Q4 was significantly higher than that in group Q1 (OR = 1.61, 95%CI:1.10, 2.34; P = 0.006). In the RCS linearity test, AIP was positively associated with the risk of PSD (Pnon-linear = 0.357). The interaction test demonstrated that AIP only had an interaction with gender (Pinteraction = 0.031) and not with other variables (Pinteraction > 0.05).Conclusion: AIP was positively associated with the prevalence of PSD, suggesting that AIP may be a promising predictor of the risk of developing PSD. In addition, the interaction of AIP and gender differences combined to influence the incidence of PSD.